The Impact of Change Management on The Quality of Health Services in Government Hospitals in Riyadh - Almutairi, Khaled Hamed; Almutairi, Youssef Abdulaziz; Almutairi, Trad Hamed; Alzaid, Mohammed Abduiih; Almutairi, Bandar Hamed; Almutairi, Bader Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of change management on the quality of health services in government hospitals in Riyadh, and to identify the reality of change management and the level of quality of health services in government hospitals in Riyadh. (143) employees of government hospitals in the city of Riyadh. The study used the questionnaire as a tool for data collection. In light of this, the study reached a number of results, the most important of which is that the square of the multiple correlation coefficient R square or the coefficient of determination is equal to (0.086) for the independent variable: (change management), and this means that this variable explains (8.6%) of the total variance in the quality of health services in government hospitals. . It also shows the validity of the model for predicting the quality of health services in government hospitals through the total degree of change management application, given the significance of the value of (P) at a low level of uncertainty (0.000) for the independent variable on the dependent variable. In light of the results, the study recommends the necessity of good and tight planning for the change process through making long-term strategic plans, with short-term goals. And the need for the change in the organizational structure to be in line with the requirements of work within the hospital, and after studying the requirements of the change, the internal and external environment carefully. And the need to pay attention to the beneficiaries’ satisfaction with the health services provided, as obtaining the beneficiaries’ information is one of the aspects of change management. And work on the automation of systems within the government sector and the development of technology that should be used inside the hospital, in order to improve the health services provided by the hospital.